The Role of Business Communication Through Online Shop Media in Increasing Consumer Buying Interest (Case Study of Makassar State University Students) - Mustari (PT FORMOSA CENDEKIA GLOBAL, 2023)
There are several approaches to business communication, including; management, economics, administrative science, communication science, or business science itself. As the use of the internet becomes more popular, so does the use of online media for marketing. The aim of this research is to study how the role of online shop media in business communication influences consumer buying interest. This kind of exploration utilizes an illustrative subjective methodology. Interviews and observations were used as data collection methods. Using a purposive sampling strategy in Makassar City, data was collected from four student informants who run online shops. According to research findings, students who operate online stores are very adept at carrying out business communications to increase consumer buying interest